Isothermal conversion of methane to methanol over CuxOy@UiO-bpy. (March 2021) - Ren, M.; Shi, Q.; Mi, L.; Liang, W.; Yuan, M.; Wang, L.; Gao, Z.; Huang, W.; Huang, J.; Zuo, Z.
Abstract: The isothermal methane oxidation to methanol over Cu oxide clusters in-situ formation in the UiO-bpy channels was investigated by experiment and density functional theory (DFT). At 200 °C, methanol yield and selectivity are 24.33 μmol/gcat and 88.1%, and the side-product is ethanol. In addition, no activity drop was observed for the Cux Oy @UiO-bpy catalyst over three consecutive cycle experiments. DFT shows that two-dimensional Cu4 O4 is the major Cux Oy species (80.85%), and the synthesis is direct reaction mechanism for methane oxidation to methanol. Graphical abstract: Image 1